Effects of Various Types of Vacuum Cold Plasma Treatment on the Chemical and Functional Properties of Whey Protein Isolate with a Focus on Interfacial Properties - Elham Ommat Mohammadi; Samira Yeganehzad; Mohammad Ali Hesarinejad; Mohsen Dabestani; Emanuel Schneck; Reinhard Miller (Colloids and Interfaces, 2023)
Vacuum cold plasma (VCP), a novel non-thermal processing technology used to modify the physicochemical properties and functionalities of food materials, was applied to whey protein isolate (WPI). The treatment affects the protein chemistry and, as a result, leads to differences in the behavior in solution and at interfaces. To minimize the undesirable effects of high oxidation and to increase the effectiveness of reactive species, the VCP treatment was applied at low pressure using different types of gases (air, combination of argon and air, and sulfur hexafluoride (SF6)). The treatment led to a decrease in the sulfur content and an increase in the carbonyl content, evidenced by oxidation reactions and enhanced disulfide bond formation, as well as cross-linking of protein molecules. Fluorescence-based indicators suggest that the hydrophobicity of the proteins as well as their aggregation increase after VCP treatment with an argon–air gas mixture; however, it decreases after VCP treatments with air and SF6. The chemical modifications further lead to changes in the pH of aqueous WPI solutions, as well as the average size and ζ-potential of WPI aggregates. Moreover, the dynamic surface tension, surface dilational elasticity, and the thickness of the WPI adsorption layers at the air/water interface depend on the VCP type. SF6 plasma treatment leads to a significant decrease in pH and an increase in the ζ-potential, and consequently to a significant increase in the aggregate size. The dynamic surface tension as well as the adsorption rates increase after SF6VCP treatment, but decrease after air–VCP and argon–air–VCP treatments. The adsorbed WPI aggregates form strong viscoelastic interfacial layers, the thickness of which depends on the type of VCP treatment.